Presenting features and early management of childhood intermittent exotropia in the UK: inception cohort study. Issue 12 (15th July 2009) - Buck, D; Powell, C; Cumberland, P; Davis, H; Dawson, E; Rahi, J; Sloper, J; Taylor, R; Tiffin, P; Clarke, M P
Abstract : Aim: To investigate factors associated with early management of intermittent exotropia (X(T)) in hospital eye departments in the UK in a prospective cohort study. Methods: An inception cohort of 460 children aged <12 years with previously untreated X(T) (mean age 3.6 years, 55.9% girls) was recruited from 26 UK hospital children's eye clinics and orthoptic departments. Participants received a standard ophthalmic examination at recruitment and orthoptic assessment at three-monthly intervals thereafter. The influence of severity of exotropia (control measured by Newcastle Control Score (NCS), and angle of strabismus, visual acuity and stereoacuity) and age on the type of management was investigated. Results: Within the first 12 months following recruitment, 297 (64.6%) children received no treatment, either for impaired visual acuity or for strabismus. Ninety-six (21%) children had treatment for impaired visual acuity. Eighty-nine (19.4%) received treatment for strabismus (22 of whom also received treatment for defective visual acuity); in 54 (11.7%) treatment was non-surgical and in 35 (7.6%) eye muscle surgery was performed. Children with poor (score 7–9) control of strabismus at recruitment were more likely to have surgery than children with good (score 1–3) control (p<0.001). Children who had no treatment were younger (mean age 3.38 years) than those who were treated (mean 4.07 years) (p<0.001). Stereoacuity and size of the angle of strabismus did not influence the type of management received. Conclusions: X(T) can be a presenting sign of reduced visual acuity. Most children with well controlled X(T) receive no treatment within 12 months following presentation.